2015
DOI: 10.1007/s10616-015-9927-0
|View full text |Cite
|
Sign up to set email alerts
|

Manool, a Salvia officinalis diterpene, induces selective cytotoxicity in cancer cells

Abstract: Manool, a diterpene isolated from Salvia officinalis, was evaluated by the XTT colorimetric assay for cytotoxicity and selectivity against different cancer cell lines: B16F10 (murine melanoma), MCF-7 (human breast adenocarcinoma), HeLa (human cervical adenocarcinoma), HepG2 (human hepatocellular carcinoma), and MO59J, U343 and U251 (human glioblastoma). A normal cell line (V79, Chinese hamster lung fibroblasts) was used to compare the selectivity of the test substance. Manool exhibited higher cytotoxic activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…In vitro and in vivo studies reported that the SAL components such as caryophyllene, α-humulene, manool, ursolic acid, and rosmarinic acid had the potential to inhibit tumor cells growth in different cell lines, prevent skin tumors formation, impede angiogenesis phases such as proliferation, migration, adhesion and tube formation. 28,30,32,[36][37][38] One of the major side effects of IFO is nephrotoxicity that can be attributed to the formation of IFO CAA metabolite. As a consequence, glomerular toxicity may develop due to the increase in blood CRT concentration and the reduction of GFR.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo studies reported that the SAL components such as caryophyllene, α-humulene, manool, ursolic acid, and rosmarinic acid had the potential to inhibit tumor cells growth in different cell lines, prevent skin tumors formation, impede angiogenesis phases such as proliferation, migration, adhesion and tube formation. 28,30,32,[36][37][38] One of the major side effects of IFO is nephrotoxicity that can be attributed to the formation of IFO CAA metabolite. As a consequence, glomerular toxicity may develop due to the increase in blood CRT concentration and the reduction of GFR.…”
Section: Discussionmentioning
confidence: 99%
“…11 Manool, a diterpene, induces selective cytotoxicity on human cervical adenocarcinoma and human glioblastoma. 34 Also, ursolic acid, a pentacyclic triterpenoid, inhibits angiogenesis, neoplastic proteases, and invasion of melanoma cells. 35 Among flavonoids of S. officinalis , rosmarinic acid has been extensively studied for its anticancer effects.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Compounds with promising therapeutic value must be able to selectively target cancer cells without affecting normal cells [37]. An anticancer agent is considered to have pharmacological or therapeutic activity if it has an SI value greater than or equal to 2 [38,39]. Compounds or drugs with SI values less than 2 are therefore considered toxic as they harm normal cells as much as or more than cancerous cells.…”
Section: Discussionmentioning
confidence: 99%